Taxation and the Quality and Quantity of Entrepreneurship - Andrea Asoni; Tino Sanandaji (Research Institute of Industrial Economics (IFN), 2009)
We study the effect of taxation on entrepreneurship, taking into account both the amount of entry and the quality of new ventures. We show that even with risk neutral agents and no tax evasion progressive taxes can increase entrepreneurial entry, while reducing average firm quality. So called success taxes increase startup of lower value business ideas by reducing the option value of pursuing better projects. This suggests that the most common measure used in the literature, the likelihood of entry into self-employment, may underestimate the adverse effect of taxation.
Keywords: H24; H25; L26; 330; Taxation; Entrepreneurial Entry; Quality of Entrepreneurial Firms; Entrepreneurship-Ansatz; Unternehmensbesteuerung; Steuerprogression; Markteintritt; Unternehmenserfolg; Theorie